Arthrobrachus crassicornis sp. nov (Coleoptera: Melyridae), a new species from the South American Transition Zone in Argentina - Estrada, Patricia (Zootaxa, 2024)
Arthrobrachus Solier, 1849 is a genus of Melyridae distributed in the southern cone of South America, with twenty valid species. A new species of the genus was recognized in the study of collection material. Artrobrachus crassicornis sp. nov. is described from Argentina and distributed in the South American Transition Zone.